Discriminatory Environment, Firms' Discriminatory Behavior, and Women's Employment in the Democratic Republic of Congo - Hyland, Marie; Islam, Asif; Muzi, Silvia (World Bank, Washington, DC, 2020)
This paper contributes to better understanding firms' discriminatory behavior in the presence of gender-based legal discrimination and its linkages with labor market outcomes for women in a developing country setting. Using data collected through the World Bank Enterprise Surveys in the Democratic Republic of Congo, the paper documents the existence of nonnegligible employer discrimination and limitations in women's autonomy in the presence of a discriminatory environment. Interestingly, these are more pervasive outside the capital city, Kinshasa, which suggests that cultural norms or differences in regulation enforcement may be at play. The paper also finds that firms' discriminatory behavior harms women's labor market outcomes, in their representation among the upper echelons of management and participation in the overall workforce. The negative relationship between restrictions from discriminatory behaviors and female employment is particularly strong in the manufacturing sector.